Anxiety, depression, and quality of life in children and adults with alopecia areata: A systematic review and meta-analysis - van Dalen, Marije; Muller, Kirsten S.; Kasperkovitz-Oosterloo, Johanna M.; Okkerse, Jolanda M. E.; Pasmans, Suzanne G. M. A. (Frontiers in Medicine, 2022)
Alopecia Areata (AA) is a non-scarring hair loss condition, subclassified into alopecia areata, alopecia universalis and alopecia totalis. There are indications that people with AA experience adverse psychosocial outcomes, but previous studies have not included a thorough meta-analysis and did not compare people with AA to people with other dermatological diagnoses. Therefore, the aim of this systematic review and meta-analysis was to update and expand previous systematic reviews, as well as describing and quantifying levels of anxiety, depression and QoL in children and adults with AA. A search was conducted, yielding 1266 unique records of which 92 were included. Review results showed that people with AA have higher chances of being diagnosed with anxiety and/or depression and experience impaired quality of life. Their psychosocial outcomes are often similar to other people with a dermatological condition. Meta-analytic results showed significantly more symptoms of anxiety and depression in adults with AA compared to healthy controls. Results also showed a moderate impact on quality of life. These results further highlight that alopecia areata, despite causing little physical impairments, can have a significant amount on patients’ well-being. Future studies should examine the influence of disease severity, disease duration, remission and relapse, and medication use to shed light on at-risk groups in need of referral to psychological care.